Evaluación de un SG-SST frente los requisitos de la Resolución 0312 de 2019, en la empresa Imperial S.A. (2021)
This report shows the results of the practice of designing an OSHMS according to the standards of Resolution 0312 of 2019 for the company Imperial S.A., as a strategy for improvement and prevention of accidents and situations that result fatal for the company and its collaborators, a qualitative methodology was carried out and the method was inductive, the main sources of information were the company and its collaborators, and the information technique was the survey through the application of a checklist of minimum standards that the company must meet according to its risk level.